2009
DOI: 10.1093/jxb/erp126
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization and biochemical comparison of cytosolic and secreted cytokinin dehydrogenase enzymes from maize

Abstract: Cytokinin dehydrogenase (CKX; EC 1.5.99.12) degrades cytokinin hormones in plants. There are several differently targeted isoforms of CKX in plant cells. While most CKX enzymes appear to be localized in the apoplast or vacuoles, there is generally only one CKX per plant genome that lacks a translocation signal and presumably functions in the cytosol. The only extensively characterized maize CKX is the apoplastic ZmCKX1; a maize gene encoding a non-secreted CKX has not previously been cloned or characterized. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 27 publications
3
60
0
Order By: Relevance
“…For example, in Arabidopsis, the only nontargeted CKX, AtCKX7, is restricted to the cytosol (Galuszka et al, 2007;Köllmer et al, 2014). Similarly, in maize, ZmCKX10 lacked a translocation signal and also localized in the cytosol (Smehilová et al, 2009). Our results demonstrated that OsCKX4 is also a cytosolic cytokinin degradation enzyme.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…For example, in Arabidopsis, the only nontargeted CKX, AtCKX7, is restricted to the cytosol (Galuszka et al, 2007;Köllmer et al, 2014). Similarly, in maize, ZmCKX10 lacked a translocation signal and also localized in the cytosol (Smehilová et al, 2009). Our results demonstrated that OsCKX4 is also a cytosolic cytokinin degradation enzyme.…”
Section: Discussionmentioning
confidence: 63%
“…to be localized in the apoplast or vacuoles, there is generally one CKX per plant genome that lacks a translocation signal and, thus, presumably functions in the cytosol (Smehilová et al, 2009). For example, in Arabidopsis, the only nontargeted CKX, AtCKX7, is restricted to the cytosol (Galuszka et al, 2007;Köllmer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The substrate binds above the isoalloxazine plane of the FAD cofactor and its amino group forms a hydrogen bond with an aspartic acid-glutamic acid (Asp-Glu) pair that facilitates the oxidation (Malito et al 2004). Studies on the substrate specificity of Arabidopsis thaliana and maize CKX isoforms revealed that not only free bases and ribosides of isoprenoid CKs, including cis-zeatin (Šmehilová et al 2009;Pertry et al 2010;Gajdošová et al 2011), but also CK 9-glucosides and nucleotides are effectively cleaved by individual isoforms (Galuszka et al 2007;Kowalska et al 2010). It was also presented that aromatic CKs are degraded by CKX as well, although with lower reaction rates (Frébortová et al 2004;Galuszka et al 2007).…”
Section: Ck Metabolismmentioning
confidence: 99%
“…cytokinin N-glucosides and cis-zeatins, with the highest decrease found in old leaves and the lowest decline in young ones. As both N-glucosides and cis-zeatins were reported to serve as substrates for the CKX (Armstrong 1994, Galuszka et al 2007, Š mehilová et al 2009) the decrease in concentrations of these derivatives in AtCKX2 plants was obviously a direct consequence of their higher degradation by the CKX activities. The levels of active cytokinin bases and ribosides were rather low even in control leaves and were not considerably altered in transformed plants.…”
Section: Discussionmentioning
confidence: 99%